In vitro evaluation of PEI-coated microbubble– neutrophil conjugates for ultrasound-guided cell delivery - Razmi Bagtash, Hossein; Gandhi, Roshni; Rastegar, Ghazal; Azizi, Amine; Jha, Aparna Priyadarshani; Shao, Shuai; Salari, Emma; Sirsi, Shashank R.; Jones, Caroline N. (Frontiers in Immunology, 2026)
BackgroundImmunotherapies have advanced cancer treatment; however, their clinical efficacy remains limited for solid tumors due to challenges associated with effectively directing immune cells into the complex tumor microenvironment. Recent developments in Ultrasound Contrast Agent (UCA — also known as “microbubble”) technology have provided novel opportunities to enhance targeted therapeutic delivery. In this study, we introduce an innovative approach of leveraging microbubbles to enhance immune cell targeting by directly attaching microbubbles to immune cells, establishing an in vitro platform to evaluate microbubble–immune cell conjugation with potential applicability to ultrasound-guided delivery strategies.MethodsTo create novel microbubble-immune cell conjugates, we created polyethyleneimine (PEI) coated microbubbles and attached them to differentiated HL-60 (dHL-60) cells. These positively charged PEI microbubbles were formulated using azide- DBCO click chemistry between DBCO-labeled microbubbles and the azide functional groups on the PEI polymer. Following this step, we utilized electrostatic interactions to attach our positively charged PEI microbubbles to our negatively charged dHL-60 cells. We conducted viability experiments to assess the compatibility of these designs and then used microfluidic chemotaxis platforms to quantify the microbubble-conjugated dHL-60 cell migratory behavior, examining parameters including migration velocity and percentage. Additionally, we investigated the impact of ultrasound power on primary human neutrophils to validate the functional responsiveness of these physiologically relevant immune cells.ResultsWe formulated our PEI microbubble-conjugated dHL-60 cells and verified that cell viability remained greater than 88% four hours after the conjugation process for different ratios of dHL-60 cells to PEI microbubbles. We found that cell: microbubble ratios of 1:1 and 1:2 produced higher migration rates compared to ratios of 1:5 and 1:10 for both dHL-60 cells and PEI microbubble-conjugated dHL-60 cells. Moreover, we found that higher microbubble binding also reduces cell velocity. Lastly, we found that cell migration remained comparable towards both chemoattractants under all ultrasound conditions tested (negative control, -30 dB, -10 dB, 0 dB) .ConclusionsHere we demonstrated the feasibility of ultrasound-compatible immune cell constructs while preserving migratory function in vitro. The novel PEI microbubble and immune cell conjugates reported in this work provide a foundation for future studies aimed at radiation-force-assisted immune cell delivery.